UV/H2O2 oxidation process optimization by response surface methodology for removal of polycyclic aromatic hydrocarbons (PAHs) from water - Malakahmad, A. (Desalination Publications, 2017)
Polycyclic aromatic hydrocarbons (PAHs) are persistent organic pollutants in water. They are categorized by International Agency for Research and Cancer as toxic, carcinogenic and mutagenic substances that can cause cancer and birth defect. This study was conducted to investigate the performance of ultraviolet radiation combined with hydrogen peroxide (UV/H2O2) for removal of PAHs from aqueous solution. The process was then optimized using response surface methodology by ranging three operating variables (hydrogen peroxide concentration, pH and reaction time) based on five-level central composite design. The significance and adequacy of the results were evaluated by analysis of variance. The model was found to be significant to give less than 0.05 probability of error and was fit with data based on insignificant of lack-of-fit test at values of 0.0005. The high R2 and adjusted R2 (0.8965 and 0.8771) revealed satisfactory adjustment of a quadratic model to experimental data. Application of UV/H2O2 process reduced PAHs concentrations in solution up to 99.4 ± 0.1. The optimum operating condition was achieved at hydrogen peroxide concentration of 1 mM, pH of 3.5 and reaction time of 90 min. The experimental data and model prediction agreed well with error less than 3. © 2017 Desalination Publications. All rights reserved.